Implementation Of Synergy Between Post Meger Employees At Indonesian Sharia Bank Gatot Subroto Branch Office Denpasar - R. Agrosamdhyo (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The purpose of this study is to find out how the synergy between post-merger employees at the BSI Denpasar Branch Office. The research methodology used is qualitative research using triangulation in testing credibility as checking data from various sources in various ways and at various times. The informants in this study were employees of the Denpasar Branch of Bank Syariah Indonesia using a purposive technique. As well as data collection in the form of: Interviews and Documentation. This study describes the results under which the synergy between employees who previously came from BNI Syariah, Mandiri Syariah and BRI Syariah was well established.